Does national policy in England help deliver better and more consistent care for those at the end of life?. Issue 4 (October 2020) - Barker, Rhiannon; Wilson, Patricia; Butler, Claire
Objectives: To explore the extent to which national policy in end of life care in England influences and guides local practice, to ensure that care for patients over the age 75 years is of a consistently good quality. Method: This paper reports on phase one of a larger study and focuses its discussion on the high-level (macro) determinants emerging from the analysis. Fifteen in-depth interviews were conducted with professionals involved in the development of English policy in end of life care. Results: Factors influencing the quality of end of life care were stratified into three system levels: meso, macro and micro. English national policy was reported to be an important macro-level determinant of effective outcomes, and examples were provided to demonstrate how policy was influencing practice. Yet, the complexity of the area and the range of interacting contributory factors mean the value of policy alone is hard to assess. At the macro-level, concern was voiced around: whether policy was effective in tackling rising inequity; lack of mandatory leverage to exert change relating to end of life outcomes; the impact of ongoing infrastructural change on statutory services; workforce pressures; over-reliance on acute services and continued abdication of responsibility for end of life care to medical professionals supported by the continued dominance of the medical model of care. Conclusions: The links between the existence of policy at the macro-level of the system and the effective enactment of good practice remain unclear, although strategies are suggested to help achieve greater national consistency in end of life care outcomes. Policymakers must pay attention to the following: controlling the rise in localism and its contribution to regional inequalities; the impact of continuous infrastructural change together with increasing workforce pressures; encouraging broader professional and public responsibility for recognition and care of those at the end of life.